Exploration of the Shared Gene Signatures and Molecular Mechanisms Between Systemic Lupus Erythematosus and Pulmonary Arterial Hypertension: Evidence From Transcriptome Data - Yao, Menghui; Zhang, Chunyi; Gao, Congcong; Wang, Qianqian; Dai, Mengmeng; Yue, Runzhi; Sun, Wenbo; Liang, Wenfang; Zheng, Zhaohui (Frontiers in Immunology, 2021)
Backgrounds: Systemic lupus erythematosus (SLE) is an autoimmune disease that can affect multiple systems. Pulmonary arterial hypertension (PAH) has a close linkage with SLE. However, the inter-relational mechanisms between them are still unclear. This article aimed to explore the shared gene signatures and potential molecular mechanism in SLE and PAH. Methods: The microarray data of SLE and PAH in the Gene Expression Omnibus (GEO) database were downloaded. The Weighted Gene Co-Expression Network Analysis (WGCNA) was used to identify the co-expression modules related to SLE and PAH. The shared genes existing in the SLE and PAH were performed enrichment analysis by ClueGO software, and their unique genes were also performed biological processes analyses used DAVID website. The results were validated in another cohort by differential gene analysis. Moreover, the common microRNAs (miRNAs) in SLE and PAH were obtained from Human microRNA Disease Database (HMDD) and the target genes of whom were predicted through miRTarbase. Finally, we constructed the common miRNAs-mRNAs network with the overlapped genes in target and shared genes. Results: Using WGCNA, four modules and one module were identified as the significant modules with SLE and PAH, respectively. ClueGO enrichment analysis of shared genes reported that highly activated type I IFN response was a common feature in the pathophysiology of SLE and PAH. The results of differential analysis in another cohort were extremely similar to them. We also proposed a disease road model for the possible mechanism of PAH secondary to SLE according to the shared and unique gene signatures in SLE and PAH. The miRNA-mRNA network showed that hsa-miR-146a might regulate the shared IFN-induced genes, which played an important role both in SLE and PAH. Conclusion: Our work firstly revealed the high IFN response in SLE patients might be a crucial susceptible factor for PAH and identified novel gene candidates that could be used as biomarkers or potential therapeutic targets.